Whole-Genome Sequencing and De Novo Assembly of 61 Staphylococcus pseudintermedius Isolates from Healthy Dogs and Dogs with Pyoderma - Francino, O. (Microbiol Resour Announc, 2021)
We have de novo assembled and polished 61 Staphylococcus pseudintermedius genome sequences with Nanopore-only long reads. Completeness was 99.25%. The average genome size was 2.70 Mbp, comprising 2,506 coding sequences, 19 complete rRNAs, 56 to 59 tRNAs, and 4 noncoding RNAs (ncRNAs), as well as CRISPR arrays.